Ambiguity, Transparency, and Institutional Strength - Erbas, S. (IMF Working Papers; Working Paper ;, 2004)
Institutional transparency makes future contingencies more easily predictable for investors. Greater transparency can be achieved through vertical and horizontal integration of policy rules, which may result in lower Knightian uncertainty (ambiguity). In a model based on cumulative prospect theory, for a given probability and payoff structure, expected return on investment is higher in more transparent countries; therefore, those countries attract more investment and grow faster than less transparent countries. Lower transparency may result in inherently higher volatility.